Faktor-Faktor Kritis Pendukung Renovasi Rumah Bersubsidi yang Berkelanjutan: A Case from Medan - Yenni Yosita Br Barus; Yani Rahmawati (Universitas Muhammadiyah Palembang, 2025)
The government provides subsidized single-story housing for low and middle-income communities. However, these houses often undergo major renovations due to residents is comfort with the housing quality. Buildings that adopt a passive design approach have the potential to enhance comfort and environmental friendliness as a sustainable and future oriented investment. Therefore, passive design is essential for achieving sustainable renovations of subsidized housing. This study focuses on three subsidized housing projects in Medan City. The research employs qualitative and quantitative approaches, collecting data through three stages: literature review, expert interviews, and field observations, including questionnaire distribution to residents of single-story subsidized housing in Medan. A Likert scale is used to assess residents needs, while a ranking system prioritizes the most efficient passive design factors for renovation.The study identifies five key passive design factors that can optimize subsidized housing: vegetation, materials, ventilation, shading, and interior layout. The findings serve as a guideline for homeowners, developers, and policymakers to construct or renovate more sustainable subsidized single-story housing.